(untitled) (Research, Society and Development, 2021)
This text derives from an approved qualitative research by the Ethics Committee. It objectifies to reflect about the speech, made in the Community Canal Púrpura on Facebook, that transmitted intolerant content, associated with political questions. The collection of data happened from August to October 2018. It was utilized the analysis of social media e the Netvizz app to locate the interactions published within the community. Of the posted content we’ve chosen those from the Ataques de Ódio album, that contained records of intolerance, hate speech and fake news directed to Canal Púrpura e its founder. The analysis of the content was due to the hermeneutic understanding. Thus, we were able to verify in the posts: records of violence as the only possible allegation for the interactions; disrespect, attempts of opinion imposition and retaliation. Thereby, the hate speech analyzed brings us to the reflection about the difference between the rights, freedom of speech and hate speech. It is considered that in these posts there was the practice of individualistic ethics that points to particular interests over the public. It’s concluded that the debate about the importance of recognizing alterity and reciprocity in interpersonal relationships is essential in confronting the expression of hatred on the web.